Prognostic significance of tPA/PAI-1 complex in patients with heart failure and preserved ejection fraction - Winter, Max-Paul; Kleber, Marcus E.; Koller, Lorenz; Sulzgruber, Patrick; Scharnagl, Hubert; Delgado, Graciela; Goliasch, Georg; März, Winfried; Niessner, Alexander (Thrombosis and Haemostasis, 2017)
Heart failure with preserved ejection fraction (HFpEF) represents a major epidemic, clinical and public health problem with rising patient numbers every year. Traditional markers for heart failure have been shown to be of limited sensitivity in patients with HFpEF, as those do not reflect pathophysiology of the disease properly. Dysregulation of haemostasis is thought to be central for the initiation and progression of HFpEF. For this reason, we aimed to assess markers of fibrinolytic activity as potential biomarkers for risk assessment in patients with HFpEF. We evaluated blood coagulation parameters in 370 patients with HFpEF included in the LUdwigshafen Risk and Cardiovascular Health (LURIC) study. Within an observation period of 9.7 years, 40 percent of these patients died from any cause. tPA/PAI-1 complex significantly predicted all-cause mortality with a hazard ratio (HR) of 1.24 (95 % confidence interval [CI] 1.04–1.47) per increase of 1 SD and cardiovascular mortality with a HR 1.26 (95 % CI 1.02–1.56) per increase of 1 SD. Both associations remained significant after adjustment for cardiovascular risk factors, N-terminal pro–B-type natriuretic peptide (NT-proBNP) and frequent HFpEF- related comorbidities. Importantly, tPA/PAI-1 complex had additional prognostic value above and beyond NT-proBNP as indicated by integrated discrimination improvement (0.0157, p=0.017). In conclusion, the concentration of tPA/ PAI-1 complex is an independent predictor of mortality from all causes and from cardiovascular causes in patients with HFpEF. The concomitant measurement of tPA/PAI-1 complex might be useful in clinical practice to add prognostic value to traditional markers of heart failure.
Keywords: Heart failure and preserved ejection fraction (HFpEF); tissue plasminogen activator (tPA); plasminogen activator inhibitor 1(PAI-1)